Short Communication: Taxonomic Profiling of Bacteria in The Bio-Enzyme That Produced From Orange Fruit Waste - Kurniawan, Andri; Mustikasari, Diah; Kurniawan, Ardiansyah; Muntoro, Muntoro; Setiadi, Jhodi; Kholishah, Nur Afifah (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2025)
AbstractFruit wastes are reported as among the main contributors to food waste production. They have an impact on the environment so they need to be treated. To reduce the negative effects, fruit wastes must be treated before they are released into the environment. Meanwhile, the fruit wastes have been reported about their functional properties and nutritional as bio-enzyme. This preliminary study aimed to provide information about metagenome bacteria of bio-enzymes from orange fruit wastes treated with different concentrations of probiotics in anaerobic fermentation. Bio-enzyme was a fermented solution made from a mixture of 15 g brown sugar: 5 kg orange fruit waste: and 12 L water. The fermentation process was carried out for 1 month and then the bioenzyme sample was taken 1 L for metagenome analysis. The metagenomic analysis was carried out using the next-generation sequencing (NGS) method for the 16S rRNA gene of bacteria by amplicon full-length sequencing with nanopore sequencing. In this research, phylum Pseudomonadota (Proteobacteria), class Betaproteobacteria, order Burkholderiales, and family Comamonadaceae were the predominant bacterial group of the bio-enzyme that produced from orange fruit waste. Identification of bacterial species in the next research becomes important to understand the role of bacterial species in the biochemical metabolism of bio-enzyme products from orange fruit waste.AbstrakLimbah buah-buahan dilaporkan sebagai salah satu penyumbang utama produksi limbah makanan. Limbah buah mempunyai dampak terhadap lingkungan sehingga perlu ditangani. Limbah buah harus diolah terlebih dahulu untuk mengurangi dampak negatifnya sebelum dibuang ke lingkungan. Sementara itu, limbah buah telah dilaporkan mengenai sifat fungsional dan nutrisinya sebagai bio-enzim. Penelitian awal ini bertujuan untuk memberikan informasi mengenai diversitas metagenom bakteri yang terdapat di produk bioenzim yang diproduksi dari limbah buah jeruk yang diberi perlakuan konsentrasi probiotik berbeda dalam fermentasi anaerobik. Bio-enzim merupakan larutan fermentasi yang terbuat dari campuran 15 g gula merah : 5 kg limbah buah jeruk : 12 L air. Proses fermentasi dilakukan selama 1 bulan dan kemudian sampel bioenzim diambil sebanyak 1 L untuk dianalisis metagenom. Analisis metagenomik bakteri dilakukan dengan menggunakan metode next-generation sequencing (NGS) untuk analisis 16S rRNA gene melalui sekuensing amplikon dengan nanopore sequencing. Pada penelitian ini, keberadaan bakteri pada bio-enzim yang diproduksi dari limbah buah jeruk. Filum Pseudomonadota (Proteobacteria), kelas Betaproteobacteria, ordo Burkholderiales, dan famili Comamonadaceae merupakan kelompok bakteri yang dominan di bio-enzim yang diproduksi dari limbah buah jeruk. Identifikasi spesies bakteri pada penelitian selanjutnya menjadi penting untuk mengetahui peranan spesies-spesies bakteri di metabolisme biokimiawi dari produk bio-enzim dari limbah buah jeruk.